1992
DOI: 10.1159/000154088
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of ORM1, C6, C7 and APO C-ll Allele Frequencies in Populations from Mainland Italy and Sardinia

Abstract: The genetic variation of the human plasma proteins ORM1, C6, C7 and APO C-II was investigated by isoelectric focusing followed by immunoblotting in populations from mainland Italy and Sardinia. The frequencies of ORM1*1 were 0.621 and 0.564, while those of C6*A were 0.657 and 0.706 on mainland Italy and in Sardinia, respectively. In the Roman sample, 8 het-erozygotes with C6 variant alleles were encountered, while none were observed in Sardinians. For C7 and APO C-II a number of heterozygotes with the rare all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

1993
1993
1995
1995

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…Nevertheless, a selective advantage a t one extreme of the environmental gradient of APOE*4-carrying genotypes is difficult to explain since they are associated with higher mean LDL-cholesterol concentrations. Sing & Davignon (1985) suggest that an advantage could depend on the tendency of APOE*4 carriers to have slightly higher HDL-cholesterol concentrations. Since HDL-cholesterol represents only a small fraction of total plasma cholesterol, a small increase may be quite meaningful.…”
Section: Population Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Nevertheless, a selective advantage a t one extreme of the environmental gradient of APOE*4-carrying genotypes is difficult to explain since they are associated with higher mean LDL-cholesterol concentrations. Sing & Davignon (1985) suggest that an advantage could depend on the tendency of APOE*4 carriers to have slightly higher HDL-cholesterol concentrations. Since HDL-cholesterol represents only a small fraction of total plasma cholesterol, a small increase may be quite meaningful.…”
Section: Population Studiesmentioning
confidence: 99%
“…Xu et al 1991 ;James et al 1993). Another mechanism (Sing & Davignon, 1985) could reside in some E4 properties. Its different distribution on lipoprotein particles and its higher catabolic rates (Gregg et al 1986) will result in a fast clearance of chylomicrons and VLDL remnants.…”
Section: Population Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Phosphoglycolate phos-(ESD), and phosphogluconate dehydroge-phatase (PGP) was studied by starch gel nase (PGD) and following Spielmann and electrophoresis following Parker and Hop- Typings of serum markers were carried out by standard procedures with minor modifications for F13A, F13B, ORM1, C6, C7, and APO C2 (Scacchi et al, , 1992 and following the method reported in Giblett (1969) for HP. The AEiO determinations on the Punjab blood specimens were performed with the standard methods.…”
Section: Phenotype Determinationsmentioning
confidence: 99%
“…The ORM1 locus has been assigned to chromosome 9q34.3-qter, and linkage to the ABO, AKJ and ALADH loci has been demonstrated [7,8], ORM typ ing employing isoelectric focusing and immunoblotting has revealed that the scrum ORM components are controlled by two dif ferent loci ORM1 and ORM2 [9], The ORM2 locus which has been found to be po lymorphic among Japanese is apparently monomorphic in other populations. Further studies have shown additional genetic varia tion including a gene duplication at the ORM1 locus and a silent allele at the ORM2 locus [10][11][12], Polymorphism at the ORM1 locus has been studied in a number of populations [13][14][15], Montiel et al [13] have summarized ORM1 al lele frequencies in different populations. The frequency of the ORMl *2 allele varied be tween 0.34 and 0.45 in most world populations including Europeans.…”
Section: Introductionmentioning
confidence: 99%